Gestão integrada e controle da dengue: o papel da comunicação e a perspectiva da Saúde Ambiental - Rodovalho, Franciele Martins (2020)
The current epidemiological scenario of deterioration in basic health indicators is a reflection of the degradation of the population's living conditions, which increasingly, in the face of the current political-economic crisis, distributing the risks of illness and dying unevenly, especially in the case of vector-borne diseases. In order to contribute to the debate on Integrated Management of Dengue Control, from the perspective of Environmental Health, with a focus on health communication actions, this study aims to contribute to overcoming the traditional epidemiological approach to Dengue - which, when prioritizing a reactive management model, investing most resources (economy and operational) in vector control actions after each outbreak or epidemic - does not prevent new cases. The methodological path was based on a basic research, with an exploratory-descriptive objective and a qualitative approach. Regarding the procedures, a documentary and bibliographic analysis was carried out, using the integrated management guidelines for the prevention and control of Dengue in the Americas as a primary source of information, a document proposed by the Pan American Health Organization in 2018 Epidemiological data and communication campaigns related to Dengue were also considered as an information base, available for consultation at virtual public domain addresses. Based on the results obtained through documentary research, we built units of analysis to discuss the results, according to the content analysis procedure. Thus, in the present study, proposals for management and communication are proposed and discussed considering (i) the failure of the current communication model; (ii) an Environmental Health perspective to face Dengue and (iii) the requirements for integrated Dengue management. In our analysis, we emphasize the criticism of the models of strategic communication and social mobilization for behavior change, adopted as a political axis for the prevention and control of dengue, which blame the population. Finally, in the present work, we present and discuss an integrated management proposal, which incorporates the perspective of analyzing the influence of environmental, social, economic and cultural determinants in the current epidemiological overview, to which the health system must respond in common.